Achieving Sustainability in Transportation Infrastructure Projects (Roads): A Nigeria Case Study - Oraegbune, M.O.; Ugwu, O.O.; Nwoji, C.U.; Ezeokpube, G.C. (Journal of Environmental Science and Engineering Technology, 2015)
This paper reports a research that investigated various challenging issues militate against successful delivery of sustainable transportation infrastructure projects in Nigeria focusing on roads. The case study method was used. In the research and several sources were used for data collection. These sources for primary data include case study based semi-structured, while secondary data sources projects, contract documents, industry publications and government reports. The research findings were used to formulate matrix of 13 vital challenging issues, and the development of a framework/roadmap and models for sustainable road infrastructure projects. The paper discusses the findings and makes some recommendations for transportation infrastructure projects sustainability.